(untitled) (Journal of the College of Basic Education, 2025)
The aim of the study is to identify the effectiveness of the Edelson model in acquiring physical concepts among fourth-grade female students in preparatory school and to develop their inferential thinking. The research consists the fourth-grade female students in public schools for the year (2024-2025). The research included (60) students with groups such as (A) as a control group studying according to the traditional method, and (C) as an experimental group studying according to the Edelson model, the research tool consisted of a concept acquisition test for physical concepts with (30) multiple-choice items. Its validity was verified, and its reliability was calculated, reaching (0.80). The inferential thinking test consisted of (30), and its validity and reliability were also verified the research suggests attempting to modernize and use new strategies in an important subject like physics.